A Picrorhiza kurroa Derivative, Picroliv, Attenuates the Development of Dextran-Sulfate-Sodium-Induced Colitis in Mice. (16th October 2012) - Zhang, De-Kui; Yu, Jian-Jie; Li, Yu-Min; Wei, Li-Na; Yu, Yi; Feng, Yan-Hu; Wang, Xiang
Abstract : Background . Free radicals and proinflammatory cytokines have been shown to play a critical role in the pathogenesis of ulcerative colitis (UC). Picroliv, a Picrorhiza kurroa derivative, has been demonstrated to have antioxidant and anti-inflammatory effect. The purpose of the study was to investigate the effects of picroliv on experimental model of UC in mice. Materials and Methods . Picroliv was administrated orally by gavage to mice with colitis induced by dextran sulfate sodium (DSS). Disease activity index (DAI), colon length, and histology score were observed. Myeloperoxidase (MPO) activity, and SOD, MDA concentrations were measured by enzyme-linked immunosorbent assay (ELISA) while the expression of cytokine mRNAs was studied by real-time-quantitative polymerase chain reaction and also ELISA. The expression of NF- κ B p65 was observed by immunohistochemistry staining and western blotting. Results . A significant improvement was observed in DAI and histological score in mice treated with picroliv, and incerased MPO activity, MDA concentrations, and the expression of IL-1 β, TNF- α, and NF- κ B p65 in mice with DSS-induced colitis were significantly reduced while decreased SOD level increased following administration of picroliv. Conclusion . The administration of picroliv leads to an amelioration of DSS-induced colitis, suggesting administration of picroliv may provide a therapeutic approach for UC.